1991
DOI: 10.1029/91jc02064
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the air‐sea exchange of CO2 in the south Pacific during austral autumn

Abstract: Measurements of CO 2 concentrations in the atmosphere and in the surface waters of the South Pacific Ocean were made by NOAA scientists between 1984 and 1989. These basin-wide measurements were all taken during austral autumn and provide data for evaluation of the seasonal flux of CO 2 from this region. The sensitivity of this flux to the uncertainty in the CO 2 gas exchange coefficient was evaluated using four different wind data sets and two formulations for the wind dependence of gas transfer velocity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…2 of Lee et al (1998) suggests that the fCO 2 -SST slope would be positive. Poisson et al (1993) found no distinguishable relationship between fCO 2 and SST in the Indian sector of the Southern Ocean, whereas Murphy et al (1991) documented variable correlations between pCO 2 and SST in the South Pacific north of 60°S. At 110°W they found a good correlation, albeit with a lower slope than this study, but at 170°W the relationship was weaker.…”
Section: Side 11mentioning
confidence: 42%
“…2 of Lee et al (1998) suggests that the fCO 2 -SST slope would be positive. Poisson et al (1993) found no distinguishable relationship between fCO 2 and SST in the Indian sector of the Southern Ocean, whereas Murphy et al (1991) documented variable correlations between pCO 2 and SST in the South Pacific north of 60°S. At 110°W they found a good correlation, albeit with a lower slope than this study, but at 170°W the relationship was weaker.…”
Section: Side 11mentioning
confidence: 42%
“…For example, how important are the organisms in the Subantarctic water ring that contributes about N0 of the ocean surface and is believed to partake significantly in the exchange of CO 2 between the atmosphere and the ocean as a whole? To my mind, the marked drawdown of CO 2 during fall in the Pacific and Atlantic sectors of the ring (Tans et al, 1990;Murphy et al, 1991) proves that during this season at least, biological processes are more important for the surface water than physically mediated ones (e.g., from temperature changes or vertical water motions).…”
Section: Regional Scope Of the Problem Of Timely Predictionmentioning
confidence: 99%
“…Recent studies on sedimentary fluxes in the southwest Pacific near the Subtropical Front indicate that the region may be a moderate biologically-mediated sink for atmospheric CO 2 (Murphy et al 1991;. The physical oceanography of the region is highly complex (Heath 1985) and the ecosystem function diverse and complex (BradfordGrieve et al 1999).…”
Section: ϫ10mentioning
confidence: 99%